Cefuroxime-induced thrombocytopenia?. Issue 854 (December 1996) - Aitken, Peter; Zaidi, SMN
Abstract : We present the case of a 77-year-old man who became thrombocytopenic whilst treated parenterally with cefuroxime in the absence of proven infection and recovered when the cefuroxime was discontinued.